Chestnuts quality online detection technology based on acoustics. Issue 7 (March 2020) - He, Wenbin; Wei, Aiyun; Ming, Wuyi; Jia, Haojie; Chen, Zhijun; Wu, Ziqiang
Abstract: In order to overcome the influence of various uncertain factors on the quality of chestnuts in the process of manual detection, an online detection method based on acoustics was proposed. In this paper, a multilevel inspection platform for chestnut surface defects based on acoustics is constructed to realize real-time acquisition and measurement of chestnut surface defects. Through acoustic detection, the sound collected from the feature area is converted into a time-frequency map, and image processing was performed using matlab software. At the same time, in the return air detection, the chestnuts with wormholes will produce a return air, which was used as the secondary detection of the chestnuts. This study provides a useful reference for chestnuts quality testing and improves the objectivity and accuracy of chestnuts quality testing.